Adolescentes usuários de drogas em CAPSad e seus familiares : trajetórias, cotidianos e desafios - Galhardi, Carina Curti (2016)
The mental health care for children and adolescents, was marked throughout history by oblivion and neglect in relation to the creation of public policies and services that encompass their needs and rights. Only after a long road still under construction and was included the children's and adolescents’ population on the agenda of public policies, the propositions and mental health discussions. However, there is much to advance and among the main challenges is the attention to adolescents in general and in particular for adolescents who abuse drugs. This study aims to understand, from the perspective of adolescents inserted in a CAPSad on the experience of this same equipment and the other insertion contexts in which transit and their expectations for the daily life and the future. The study search identify, from the perspective of families of adolescents to experience drug use by adolescents and their expectations for the CAPSad. This is a cross-sectional, exploratory study with a qualitative approach. Study participants were 8 adolescents and 15 families of adolescents inserted in a CAPSad located in a municipality in the state of São Paulo. It was used as methodology participant observation in which the researcher stayed and participated in the activities of the service for five months, where forms of identification, daily records of field and semi-structured interviews with adolescents and their families were hired. The material obtained across the interviews, conducted the analysis through the Collective Subject Discourse Technique (DSC) and the information from the service identification forms and adolescents and the field diary, analyzed and categorized. Among the results, it was found that drug use is present in the daily lives of adolescents and added to it there was other vulnerable situations such as prolonged hospitalization in clinics for addiction and no insertion in the school environment, which contribute to exclusion of this population, reducing the engagement possibilities and activities in other contexts. It was found that the adherence of adolescents service is low, the supply of care actions aimed at them is fragile and limited by issues of different orders as unwillingness and / or interest in addressing the teenage population, different views on the harm reduction strategy, difficulties in performing activities in partnership with other services of the municipal network, lack of action in the territory and opportunities for discussion and training. It was found that the participation of adolescents and family as co-responsible for their care actions is still absent in the service and understood as a challenge. However, it was revealed that both teenagers as family, although point limits, understand the care offered by CAPSad as a support and alternative space to meet the challenges of daily life. This study advances to reveal, from the perspective of adolescents themselves and their families, the challenges relating to the care of this population in CAPSad and, in addition to this equipment, to address the daily life of these adolescents and their families and reveal about the limits and possibilities of social participation. It is hoped that this study fosters discussions and contribute to the realization and development of public policies for this population.